Islamism and Post-Islamism: âNon-Muslimâ in Socio-Political Discourse of Pakistan, the United States, and Indonesia - Harmakaputra, Hans Abdiel (Al-Jamiah: Journal of Islamic Studies, 2015)
Islamism is defined by Asef Bayat as ideologies and movements that strive to establish some kind of an âIslamic order,â in the form of a religious state, sharia law, or moral codes. However, Bayat and other scholars have found that nowadays Islamism is changing and many countries share the traits of post-Islamism instead of Islamism. According to Bayat, post-Islamism is both condition and project to âconceptualize and strategize the rationale and modalities of transcending Islam in social, political, and intellectual domains.â In short, it has a hybrid tendency to combine Islam and democracy. This paper will discuss how the category of ânon-Muslimâ is taken place in the socio-political discourse of Islamism and post-Islamism. To limit the discussion, there are only three examples from Pakistan, the United States, and Indonesia.[Islamisme menurut Asef Bayat adalah ideologi dan gerakan yang berjuang untuk membentuk semacam âtatanan Islamâ dalam bentuk negara Islam, hukum syariat, atau pun hukum etis. Saat ini, islamisme telah berubah. Di beberapa negara muncul gejala post-islamisme yang khas. Bayat mendefinisikan post-islamisme sebagai kondisi dan keinginan untuk mengkonsep alasan dan modalitas untuk mengusung Islam ke ranah sosial, politik, dan keilmuan. Sehingga, muncul pula kecenderungan untuk menggabungkan Islam dan demokrasi. Tulisan ini mendiskusikan konsep ânon-muslimâ dalam wacana sosial politik terkait dengan Islamisme dan post-Islamisme. Pembahasan dibatasi pada tiga contoh dari Pakistan, Amerika Serikat, dan Indonesia.]